Monitoring Data Nilai Gizi Balita menggunakan Tableau Public (Studi Kasus : Posyandu Sedap Malam) - Akbar, Yuma; Azzahra, Yasmin Aulia; Hartinah, Suci Sugih; Arfadhillah, Zahra (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
In Indonesia, there are still toddlers with poor nutritional status. Nutrition is food substances needed for the development, growth, and health of a person's body. Toddlers who experience nutritional problems will have an impact on their growth and development, be susceptible to disease, and can even result in death in children under five. Children's growth and development are monitored regularly to detect potential problems early. Utilizing a community-based health system such as Posyandu is the most important key to improving the quality of children's growth and development. Monitoring of children's growth and development in Indonesia is carried out by measuring body weight every month at Posyandu with the Healthy Way Card (KMS) as a supporting tool. Through KMS, growth and development disorders in children can be identified early and appropriate steps can be taken to correct these problems. The Berbabis Tablue Posyandu Service Analysis Information System can help monitor data and information on the nutritional status of each child. The results of this paper show that the use of Tableau in analyzing data on the nutritional status of toddlers can provide a comprehensive and in-depth picture. Interactive visualization allows users to explore data directly, identify patterns, and quickly retrieve important information. With visualization, posyandu cadres can make decisions regarding toddler nutrition programs